Pengaruh Likuiditas Dan Solvabilitas Terhadap Profitabilitas Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015 - Aminar Sutra Dewi (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2018)
This study aims to determine there is the influence of liquidity and solvency ratio on profitability. This type of research is quantitative research that is data in the form of numbers. Population in this study is all food and beverage companies listed on the Indonesia Stock Exchange amounted to 14 companies. The sample in this study amounted to 12 food and beverage companies listed on the Indonesian Stock Exchange. The technique of data analysis that is used is multiple linear regressions by using program Eviews. From the results of tests conducted show that: 1) liquidity has a positive and significant impact on profitability, which is shown by probability > 0,05 is 0,9744. 2) Solvency has a positive and significant effect on profitability, which is shown by probability > 0,05 that is 0,5041. Where the R2 (R-Square) value is 1,36%.